(untitled) (Research, Society and Development, 2022)
The objective was to investigate the influence of different kinds and formats of nutrition labels on health care. This integrative review retried articles indexed in the electronic databases of the Virtual Health Library (VHL), Capes Periodicals, Google Scholar and in the National Library of Medicines (NLM) – Pubmed/Medline and SciELO databases. The 36 papers were obtained to compose this integrative review. Studies indicate that warning labels have been shown to be more effective behavior, due to the ease of understanding by consumers. Interestingly, variables such as female, having at least a college degree, being older and practicing physical activity were associated with greater interest in the use of labels. From the results explained in this integrative review, it appears that food labeling is a health promotion tool and potentially useful in the management of how people with chronic non-communicable diseases can make healthier food choices and in accordance with its limitations. The use of a language accessible to different social classes is a measure that needs to be widely adopted, in order to benefit all consumers.